Réponses

2013-06-01T01:30:48+02:00
(7d-1)(2d+9)=14d^2+63d-2d-9=14d^2+61d-9

8(2c+4)+(3c+2)(4c-7)=16c+32+12c^2-21c+8c-14=12c^+3c+18

-2(k-3)(7+3k)=(-2k+6)(7+3k)=-14k-6k^2+42+18k=-6k^2+4k+42

3(5h-3)(7h+4)=3(35h^2+20h-21h-12)=3(35h^2-h-12)=105h^2-3h-36

6(a+2)(a-5)+(2a-3)(a+4)=(6a+12)(a-5)+2a^2+8a-3a-12=6a^2-30a+12a-60+2a^2+5a-12=8a^2-13a-72

(3f+1)(2-4f)-(4f+1)(3-4f)=6f-12f^2+2-4f-(12f-16f^2+3-4f=-12f^2+2f+2-12f+16f^3-3+4f=4f^2-6f-1

5(h+5)(7h+2)+2(3h+7)(5-2h)=5(7h^2+2h+35h+10)+2(15h-6h^2+35-14h)=35h^2+10h+175h+50+30h-12h^2+70-28h=23h^2+187h+120

2(3-5h)(2h+4)-(h-9)(2-3h)=(6-10h)(2h+4)-(2h-3h^2-18+27h)=12h+24-20h^2-40h-2h+3h^2+18-27h=-17h^2-57h+42